A Pragmatic Analysis of FPRRD’s Quad Committee Hearing on Drug War Using Grice’s Maxims - Dalgan, Haninnah; Kahar, Yusrha; Tulud, Donnie; Amilbahar, Rezeille May (International Journal of Language and Literary Studies, 2025)
This study was conducted to analyze former President Rodrigo Duterte's responses during the Quad Committee hearing on the Philippine drug war through the lens of Grice's conversational maxims. An analysis of Duterte's dialogue revealed frequent violations of the maxims of Quantity, Relation, Manner, and Quality. These violations manifested as excessive, ambiguous, or irrelevant information, evasion of direct answers to critical questions posed by Congresswoman Brosas, and diversion from the central topic of inquiry. This behavior aligns with existing research indicating politicians may strategically avoid conversational maxims to evade cooperation. The study reveals that violations can undermine clarity and relevance in high-stakes political discussions, hindering effective discourse and accountability. Furthermore, the study suggests further research should focus on the strategic use of maxim violations in political contexts, their impact on public perception, and methods for enhancing clarity and transparency in political communication to foster more productive exchanges. Overall, with the help of conversational maxims and observed violations, it is easier to understand how political discourse can be manipulated to obscure accountability and hinder transparency.